Uji Organoleptik dan Kandungan Fe Pada Kopi Biji Kurma - Gianing, Dwene Nur; Eliska, Eliska (Puslitbang Sinergis Asa Professional, 2023)
Due to the known benefits and nutritional content of date seeds, the use of date seeds is not yet widespread. Date palm seeds can be processed into decaffeinated date coffee, making it safe for general consumption, and its iron content helps overcome anemic problems. The study aims to determine the sensory results and nutritional content of iron in date coffee. This research method uses a true experimental design with a post-test-only control group design that is analyzed descriptively. The study was conducted in three ways: product development stage, acceptance test, and laboratory iron nutrient content test. As a result of the sensory test, color preference was 36.0%, flavor preference was 28.0%, texture preference was 44.0%, and taste preference was 40.0%. Iron nutrient content test results were determined per 100 grams of date coffee powder with an iron content of 42.5 mg. Based on the overall sensory results of date coffee, it is generally acceptable in terms of color, aroma, texture and taste. In addition, it meets the requirement for